EFL students"™ perceptions on the use of Instagram to foster learner autonomy in speaking - Dewi, Rohmatul Fitriyah; Fajriyah, Latifatul; Abidah, Darini Yusrina (Journal of English Education Program, 2024)
To perceive the 21st  century and digital literacy issue,  Instagram  could be one of the solutions to engage learners"™ autonomy in the learning process, especially in speaking performances. However, few studies are concerned with the relationship between speaking performance and learner autonomy. Therefore, this current study intends to know the non-English major students"™ perceptions of the utilization of  Instagram as  digital literacy, their learning autonomy toward  Instagram, and their"™ speaking performances in utilizing  Instagram.  This research used a qualitative approach. The data were obtained through interviews and observations to gather richer and deeper information about the issues. Data were analyzed in three stages: reduction, display, and verification. The study results revealed that understanding the use of digital literacy was basic knowledge for students. It was because the students, as the users of those literacies, could be left behind in their daily activities. Moreover, students believed that blending digital literacy had positive impacts, including increased communication abilities, autonomy awareness, and readiness for future technology needs in the learning process and academic setting. The  Instagram  account was not just ordinary social media, it was not only an influential medium that carried engagement and interactivity among users but also covered interesting ways of serving as a powerful medium for self-expression. As a result,  for students, the utilization of  Instagram  achieved a benefit in enhancing their learners"™ autonomy in the aspects of learners"™ confidence and creativity.